The letter in Galician language from Magdalena García de Ogando to Martin Sarmiento. Interpretative edition and brief linguistic comment - Mariño Paz, Ramón (Madrygal. Revista de Estudios Gallegos, 2014)
A photographic reproduction and an interpretative edition of the letter in Galician language that Magdalena García de Ogando wrote to Martín Sarmiento, probably not long after October 1755, are presented in this article. Besides, a brief linguistic analysis of the text is carried out.